2022
DOI: 10.1007/s00432-022-04059-1
|View full text |Cite
|
Sign up to set email alerts
|

Apalutamide and autophagy inhibition in a xenograft mouse model of human prostate cancer

Abstract: Background Apalutamide (APA) is a next-generation androgen receptor antagonist for the treatment of advanced prostate cancer. We have previously shown that upregulation of autophagy is one of the mechanisms by which prostate cancer (PC) cells survive APA anti-tumor treatment in vitro. Therefore, we investigated the characteristics of the autophagic response to APA treatment, alone and in combination with autophagy inhibition, in an in vivo model. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These results from Eberli et al [78,79] strongly suggest the cytoprotective autophagy is being induced by apalutamide in LNCaP cells either in vitro, or after being implanted in mice models, highlighting the possible targeting of autophagy to increase the effectiveness of apalutamide. Although promising, a major limitation for these studies, as well as that of Boutin et al [55], is the utilization of a single cell line, LNCaP cells, which may limit the generalization of these results to other prostate cancer cell lines and the clinical situation.…”
Section: Apalutamide and Autophagymentioning
confidence: 89%
See 2 more Smart Citations
“…These results from Eberli et al [78,79] strongly suggest the cytoprotective autophagy is being induced by apalutamide in LNCaP cells either in vitro, or after being implanted in mice models, highlighting the possible targeting of autophagy to increase the effectiveness of apalutamide. Although promising, a major limitation for these studies, as well as that of Boutin et al [55], is the utilization of a single cell line, LNCaP cells, which may limit the generalization of these results to other prostate cancer cell lines and the clinical situation.…”
Section: Apalutamide and Autophagymentioning
confidence: 89%
“…However, some patients do not respond to this therapy, and eventually become resistant. Recently, Eberli et al [78,79] studied the potential targeting of autophagy to increase the effectiveness of and possibly overcome resistance to apalutamide both in vitro and in vivo.…”
Section: Apalutamide and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…PCa cells use autophagy as a survival mechanism in response to apalutamide treatment. This induction of autophagy is associated with increased expressions of Beclin1 and ATG5 proteins, and with the autophagy-related conversion of the microtubule-associated protein light chain 3 (LC3I to LC3II), the main regulators of autophagy in PCa [ 15 ]. Classic studies have indicated that at least two mechanisms underlie ADT-stimulated autophagy: one in which ADT induces local vasculature degeneration and hypoxia; and another in which, upon energy deficiency caused by ADT, AMP-activated protein kinase (AMPK) activation leads to mTOR pathway suppression and the promotion of autophagy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Determining efficacy and safety is critical during the initial phases of drugs discovery and development, and ultimately for approval and commercialization. Some of the drugs approved by the FDA or EMA, and listed above, were tested in rodent models (92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102).…”
Section: Current Therapies For Prostate Cancermentioning
confidence: 99%